The world cup in football and the US IPO market - Fjesme, Sturla Lyngnes; Lv, Jin Roc; Shekhar, Chander (Journal of Corporate Finance, 2023)
We document that US IPOs that take place during a world cup in football (soccer), compared to IPOs before or after, exhibit 9% lower underpricing and 6% lower price adjustment. IPOs during world cups receive less attention from foreign investors and exhibit significantly higher long-run returns. Our results are robust to excluding the IPO bubble period of 1999 and 2000, including only listings during summer months, controlling for overall market sentiment and market conditions, and to using various matched samples of non-world cup IPOs. Firm characteristics of world cup IPOs are indistinguishable from those of non-world cup IPOs, suggesting that selection is not driving the results. Consistent with prior studies showing that world cups affect market sentiment, we show that this extends to US IPOs, where lower sentiment, driven by foreign investors, leads to reduced investor attention and lower valuations.